Tani Terkini: Sistem Monitoring dan Kontrol Pertanian Pintar Berbasis IoT Menggunakan ESP32 - Iin Darmiyati; M Abdy Saputra; Andi Maulana; George Nathaniel Putra Aribowo; Ain Sahara; Fitri Oktafiani (Kodepena (Komunitas Dosen Penulis dan Peneliti Indonesia), 2026)
This study presents the design and implementation of an Internet of Things (IoT)–based monitoring and control system using an ESP32 microcontroller. The system is developed to monitor environmental conditions through a DHT22 sensor for air temperature and humidity measurement, as well as a pH sensor to determine the acidity level of the medium. Sensor data are transmitted to a web-based application and displayed in real time in the form of numerical values and graphical representations to facilitate user observation. In addition to monitoring functions, the system incorporates relay-based control to operate a fan and an aerator in both manual and automatic modes. System testing was conducted to evaluate the performance of sensor data acquisition and the execution of control commands. The test results indicate that the system is able to reliably read sensor data and perform control operations as intended. This system is expected to serve as a learning platform for understanding basic IoT implementation and simple control systems in agricultural applications.